2019
DOI: 10.3389/fmicb.2019.01095
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Biogas Process Modeling by Resolving Intracellular Metabolic Activity

Abstract: The process of anaerobic digestion in which waste biomass is transformed to methane by complex microbial communities has been modeled for more than 16 years by parametric gray box approaches that simplify process biology and do not resolve intracellular microbial activity. Information on such activity, however, has become available in unprecedented detail by recent experimental advances in metatranscriptomics and metaproteomics. The inclusion of such data could lead to more powerful process models of anaerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Such an approach was attempted earlier by introducing 10 artificial microbial species within each functional group of the ADM1 and varying the specific maximum substrate utilization rate and the half saturation constant (Ramirez et al, 2009). Weinrich et al (2019) elaborated on this idea by using the unique metabolic potential of real methanogenic archaea species and predicted thousands of metabolic fluxes with flux-based analysis. Neither study considered the effect of temperature, which greatly influences methanogenic activity (Elsgaard et al, 2016) and hydrolysis rate (Donoso-Bravo et al, 2009).…”
Section: Implications For Model Developmentmentioning
confidence: 99%
“…Such an approach was attempted earlier by introducing 10 artificial microbial species within each functional group of the ADM1 and varying the specific maximum substrate utilization rate and the half saturation constant (Ramirez et al, 2009). Weinrich et al (2019) elaborated on this idea by using the unique metabolic potential of real methanogenic archaea species and predicted thousands of metabolic fluxes with flux-based analysis. Neither study considered the effect of temperature, which greatly influences methanogenic activity (Elsgaard et al, 2016) and hydrolysis rate (Donoso-Bravo et al, 2009).…”
Section: Implications For Model Developmentmentioning
confidence: 99%
“…Instead of simple comparisons of resulting biomethane production, the modeling approach can provide a step forward towards an impartial routine comparison of the results obtained from a larger number of experiments. The results of biomethane production curve models described in Table 4 can more readily be coupled and compared with results from other studies as was suggested only recently (Weinrich et al, 2019;Elagroudy et al, 2020). Significant differences between the models were also observed for maximum rate methane production, where the Transfer model's estimations were up to 196% higher than those of the logistic model.…”
Section: Resultsmentioning
confidence: 79%
“…In addition, the flux-balance analysis of the methanogens actively was continuously updated in ADM1. As a result, this hybrid model could provide detailed information regarding the activity pathways in anaerobic digestion compared to the original ADM1 and could predict the intracellular activity of microbial species that are compatible with experimental data obtained from meta-genomic and meta-transcriptomic analysis [176].…”
Section: Development Of Metabolic Models and Main Gaps In The Fieldmentioning
confidence: 74%